Analisis Strategi Pengaturan Parking Stand dalam Mengatasi Over Capacity Pesawat oleh Unit Apron Movement Control (AMC) Bandar Udara Halim Perdanakusuma Jakarta - Nur Ana Putri Fidyah; Rosiana Ulfa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Halim Perdanakusuma Airport in Jakarta handles various types of flights, ranging from commercial, military, and private to state-related flights, with an average volume of 70 aircraft movements per day. The available parking stand capacity is limited to 16 stands—comprising Alpha 1–3 and Bravo 1–13—which is insufficient to accommodate the high frequency of flights. This imbalance leads to recurring overcapacity, triggered by the closure of the South Apron for state activities, the issuance of NOTAMs, changes in charter flight schedules, and delays in Ground Handling Services. Without proper management, these conditions risk causing aircraft congestiOn On the apron and taxiway, the potential for Ground collisions, and ongoing flight delays. This study aims to identify the impact of overcapacity On flight Operations and to analyze the strategies employed by the Apron Movement Control (AMC) unit in managing limited parking stands. The method used is qualitative descriptive, with data collectiOn through field observations, interviews with three key informants from the AMC unit, and a review of Apron Movement Sheets (AMS) and Daily Flight Schedules. Data validity was tested through triangulatiOn of sources and techniques, while data analysis was conducted using the SWOT framework. The research findings indicate that overcapacity leads to aircraft queues, increased risk of Ground incidents, and persistent flight delays. The AMC unit addresses this situatiOn through strategies such as repositioning aircraft to the South Apron or New South Apron, utilizing remote areas for narrow-body aircraft, prioritizing parking based On schedules, and actively coordinating with airlines, Ground Handling providers, and ATC. This study concludes that the success of managing overcapacity is largely determined by the flexibility of AMC strategies and the quality of synergy among Operational units in maintaining flight safety and smooth Operations.